Factors influencing student’s social entrepreneurship intention: a case of Duta Jauhar / Nur Syafinaz Rashid - Rashid, Nur Syafinaz (Faculty of Business and Management, 2018)
To be a social entrepreneur, it would be much better if the intention to become a social entrepreneur start at the early age. Nowadays, there is increasing number of programme to create youngster to become social entrepreneurs in future. Notice that, increase in number of young social entrepreneurs in Malaysia also occur. A part from that lack of establish social organization happen in Malaysia.